Long-term safety and efficacy of rituximab in 7 Japanese patients with ANCA-associated vasculitis. Issue 4 (July 2015) - Nagafuchi, Hiroko; Atsumi, Tatsuya; Hatta, Kazuhiro; Muso, Eri; Takeno, Mitsuhiro; Yamada, Hidehiro; Ozaki, Shoichi
Abstract: Objectives. The safety and efficacy of rituximab were examined in a multicenter open-label pilot study in patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) in Japan. Methods. Patients with refractory AAV were administered a rituximab infusion at a weekly dose of 375 mg/m 2 for 4 weeks. All patients also received oral daily prednisolone. The primary outcome was complete remission, which was defined as a Birmingham Vasculitis Activity Score (BVAS) of 0 or 1. Results. The mean age of the 7 patients was 57 (range, 34–71) years. The mean follow-up period after rituximab treatment was 62.9 (range, 4.8–81) months. The mean BVAS at entry was 16.7 (range, 2–34). Complete remission occurred in all cases, except in 1 case in which the patient died, with a significant decline in BVAS from baseline at 12 months after initiation of rituximab. Rituximab reduced granulomatous orbital involvement in a patient with granulomatosis with polyangiitis. Relapse occurred in five patients. Adverse events included de novo hepatitis B in one patient, cancer (hepatocellular carcinoma and prostate cancer) in two patients, and transient visual disturbance, atypical mycobacterial infection, urinary tract infection, sepsis, and cytomegalovirus infection. Two patients died due to recurrent infections and airway obstruction, caused by an AAV lesion. Conclusions. Rituximab had a beneficial effect on refractory AAV in Japanese patients, but several adverse effects occurred during rituximab treatment.